FACTORS THAT INFLUENCE MANAGERIAL OWNERSHIP ON COMPANY VALUE IN FOOD AND BEVERAGE SUBSEctor COMPANIES LISTED on THE BEI IN 2019-2022 - Angel Jesslyn Joe; Nina Purnasari; Kelly Faustine; Rini Herliani (Journal Accounting International Mount Hope, 2024)
This research aims to analyze the influence of dividend policy, debt policy, company size and profitability on company value both partially and simultaneously in food and beverage companies listed on the BEI in 2019-2022. The research method used is a quantitative research method with secondary data types. The analysis technique used is multiple linear regression analysis technique. The population was 59 companies and a side purposive technique was used which produced a sample of 19 companies with a research period of 4 years, resulting in a total sample of 76. The results of the study showed that dividend policy, debt policy and company size did not partially influence company value, whereas Profitability has a partial effect on company value. Simultaneously, dividend policy, debt policy, company size and profitability influence company value.